2014
DOI: 10.1155/2014/135416
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Screening for Cytomegalovirus: An Effective Preventive Approach

Abstract: Congenital cytomegalovirus (CMV) is the leading infectious cause of sensorineural hearing loss and delayed psychomotor development. Viral transmission to the fetus is far more likely to occur following a primary than a secondary maternal infection. Primary prevention seems to be the best means to reduce the burden of congenital CMV due to the lack of treatment options during pregnancy. We evaluated this approach on a cohort of 500 women planning pregnancy who attended our fertility clinic. Of the 444 who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Should these women become pregnant again, it is less likely they will be inadvertently exposed to CMV. Indeed, in a population of women receiving fertility treatment, preconception screening and counseling seemed to have the potential to reduce CMV exposure in pregnancy ( Reichman et al, 2014 ). Preconception testing would also reduce problems arising from the detection and interpretation of CMV-specific IgM antibody in an already pregnant woman ( Revello and Gerna, 2002; Guerra et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Should these women become pregnant again, it is less likely they will be inadvertently exposed to CMV. Indeed, in a population of women receiving fertility treatment, preconception screening and counseling seemed to have the potential to reduce CMV exposure in pregnancy ( Reichman et al, 2014 ). Preconception testing would also reduce problems arising from the detection and interpretation of CMV-specific IgM antibody in an already pregnant woman ( Revello and Gerna, 2002; Guerra et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a vaccine to prevent infection, a greater focus on education and prevention strategies for cCMV infection are needed for women intending to become pregnant, those already pregnant, and healthcare professionals alike. Preconception screening in those attending a fertility clinic, with resultant counseling to improve personal hygiene in those who were not immune to CMV, has shown that hygiene counseling (albeit in this highly selected cohort) is effective in reducing CMV exposure (79). In pregnant women, hygiene counseling of CMVseronegative pregnant women significantly prevents maternal infection (11).…”
Section: What Are the Gaps In Our Understanding?mentioning
confidence: 99%
“…Ideally, all women should be tested for CMV antibody and informed before pregnancy. Indeed, in a population of women receiving fertility treatment, preconception screening and counseling, seems to have a risk reduced to CMV infection in pregnancy [46]. Moreover, preconception testing would also reduce problems arising from the detection and interpretation of CMV-speci c IgM antibody in pregnant woman [47,48].…”
Section: Discussionmentioning
confidence: 99%